Especiação química de As e Cd por HPLC-ICP-MS em forrageira Brachiaria brizantha Stapf. cv. Marandu cultivada em solo previamente contaminado - Amaral, Clarice Dias Britto do (2014)
Recent research and advances in analytical chemistry show that the total content determination of an element, although it is essential, is limited since it is not sufficient to provide information about the bioavailability and toxicity of the species. Furthermore, plants are usually the main route of chemical elements (essential or toxic) entry in the food chain. Arsenic speciation in plants is important since it can be found in inorganic forms, more toxic, or methylated forms, less toxic. Moreover, both As and Cd can bind to phytochelatins (tri peptides) that are formed in plant tissue as a defense mechanism to the stress caused by potentially toxic elements. This research project aimed the determination and speciation of As and Cd in Brachiaria brizantha cv. Marandu forage grown in previously contaminated soil. In the first part of the work, these contaminants were added to the soil and after a certain period of time the forages were harvested, frozen-dried and ground in freezer mill containing liquid N2. As well as it was determined the total content of As and Cd by ICP-QMS. The mean concentrations found were 2.3 ± 0.27 mg kg-1 of As and 2.9 ± 0.07 mg kg-1 of Cd. In the second part of the work, the separation and identification of As(III), As(V), MMA (monomethylarsonic acid), and DMA (dimethylarsinic acid) species were performed using an anion exchange column and HPLC-ICPMS. Different sample preparation involving water, diluted nitric acid solution and a water methanol mixtures were evaluated in order to extract As species in plant samples. The interference standard (IFS) method using 83Kr+, was employed to minimize spectral interferences on 75As+ determination caused by polyatomic species such as 40Ar35Cl+. The procedure that presented the best xiv performance was the one using nitric acid solution with extractions carried out at 90 ºC, an efficiency of 90 % and quantitative extraction of all four As species were achieved. Improvement in accuracy from 77 % to 94 % was obtained using the IFS method. The third part of the work evaluated the As species stability in samples stored under different temperatures along 12 months, with periodical determination of them (each two months). It can be concluded that for As species evaluated, lyophilization and frozen-dried were the best sample preparation strategies. Sample storage at low temperatures resulted in poor extraction efficiency, furthermore, the sample particle size was the critical factor for choosing the best processing and storage procedure of sample. The fourth part addressed the evaluation of As-phytochelatin and Cd-phytochelatins species using HPLC-ICP-MS for the isotopes determination and HPLC-ESI-MS in order to do the phytochelatins analysis. Phytochelatins were not found in the samples stored for long periods, even at low temperatures, which demonstrates the species instability. Freshly-harvested and extracted samples were analyzed by ESI-MS and mainly glutathione (m/z 308); the phytochelatins PC2 (m/z 540) and PC3 (m/z 772), their respective oxidized forms and the compound As-PC3 (m/z 844) were found among roots, leaves and stems. The new legal requirements and trade restrictions require the development of analytical procedures to measure metalloid species in a variety of animal and plant tissues. With the combination of techniques such as ICP-MS and ESI-MS coupled to HPLC has become feasible the determination of uncommon species.